Business in the Front, Crypto in the Back: How the Blockchain Startup, Novera, Is Innovating upon Traditional Finance - Kim, Henry; Sengupta, Ushnish; Laskowski, Marek (Senate Hall, 2021)
We present the journey of Novera Capital, a blockchain start-up, that partnered with Finco, an SME investment firm actively looking for opportunities to leverage disruptive technologies. The key to this journey is expressed in Novera's "Business in the front, crypto in the back" perspective. Finance is a highly regulated and conservative sector. Novera would not have been able sell its concept for a novel bitcoin tracking fund that received seven figures in venture capital without its corporate ethos. Novera is able to clearly demonstrate compliance to regulations, and moreover show that their business practices would meet stringent expectations of large financial institutions. At the same time, it is Novera's vision to innovate beyond the fund to a blockchain-based token platform that keeps its team of technologists motivated and forward-looking. We advise others weighing investment in blockchain, especially SMEs and start-ups in finance, to understand and manage this dichotomy.
Keywords: finance|bitcoin|blockchain|start-ups|SME